Políticas públicas educacionais do governo federal nos anos de 2019 e 2020: uma análise dos fundamentos ideológicos - Machado, Gilson Batista (2021)
This study is part of the State, Policies and Education Management research line of the Postgraduation Program on Education of the Federal University of Uberlândia and had the following problematizing question: what are the ideological foundations that support the “bolsonarista” thinking, and how do they materialize in the educational policies of the federal government during the years 2019 and 2020? More specifically, serving as a theoretical foundation to support the analysis of a central question, a series of specific objectives were listed, namely: to present a theoretical-conceptual basis related to the categories, State, Public Policy and Ideology; to clarify the constitutive elements in the construction of political myths; to describe and analyze, historically, the phenomena that impacted the rise of Jair Bolsonaro to the Presidency of the Republic; to describe Jair Bolsonaro’s life, military and political trajectory; to list and describe the main discursive targets related to the educational area that were present in Bolsonaro's campaign messages; and to analyze the public policies proposed by the Jair Bolsonaro administration during the years 2019 and 2020. As a methodological path, the precepts of a research with a qualitative, descriptive and critical approach were used, also resorting to the formalities of bibliographical and documentary research. The framework of selected sources to reference this study comprised different formats, such as: articles published on different sites, profiles on social networks, videos, audios, laws, dossiers, books, articles, theses and dissertations. After selecting the sources, they were analyzed and their information collated to formulate answers to the central question and specific objectives. Among the main findings of this research, gaps were identified in the life story of Jair Bolsonaro and which, when filled in by the literature, seem to intend a remodeling of past history, fitting information relevant to the contemporary in order to assist in the imagery construction of a political myth. The literature showed relevant information regarding the myths construction, dividing the process into four constellations: the Conspiracy myth, the Savior myth, the Golden Age myth and the Unity myth. The theory pertaining to these myths was raised and later compared with the postures and speeches of Jair Bolsonaro, resulting in the conclusion that the dictates of a political myth construction fits Bolsonaro's accession to the Presidency of the Republic. During his parliamentary life, campaigning and subsequent election to the Presidency of the Republic, Jair Bolsonaro armed himself with attacks on issues closely linked to brazilian public education and, according to a preliminary hypothesis, presented proposals that were ideologically impregnated with his vision of education. It is believed, therefore, that the “bolsonarista” thinking is based on ideological foundations focused on meritocracy, authoritarianism, sectarianism, reactionaryism, neoliberalism, conservatism and, embodied, are materialized in educational public policy proposals impregnated with this essence: Student ID, the implementation of National Program of Civic-Military Schools (Pecim), the National Literacy Policy (PNA), Home Education (Homeschooling) and the Entrepreneurial and Innovative Institutes and Universities Program (Future-se).